2023
DOI: 10.1038/s41586-023-05994-w
|View full text |Cite
|
Sign up to set email alerts
|

The nature of an ultra-faint galaxy in the cosmic dark ages seen with JWST

Guido Roberts-Borsani,
Tommaso Treu,
Wenlei Chen
et al.

Abstract: In the first billion years after the Big Bang, sources of ultraviolet (UV) photons are believed to have ionized intergalactic hydrogen, rendering the Universe transparent to UV radiation. Galaxies brighter than the characteristic luminosity L* (refs. 1,2) do not provide enough ionizing photons to drive this cosmic reionization. Fainter galaxies are thought to dominate the photon budget; however, they are surrounded by neutral gas that prevents the escape of the Lyman-α photons, which has been the dominant way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Our deeper data allow us to find z > 8 galaxy candidates at fainter magnitudes, probing lower luminosities than previous works (see Section 4). Our sample, plotted in red in Figure 3, is compared with other photometrically selected candidates and the four first spectroscopic confirmations at z > 10 provided by JWST (Curtis-Lake et al 2023; Arrabal Haro et al 2023aHaro et al , 2023b as well as faint lensed galaxies above z ∼ 7 confirmed with NIRSpec spectroscopy (Langeroodi et al 2022;Carnall et al 2023;Roberts-Borsani et al 2023;Williams et al 2023). We have seven candidates in the magnitude regime probed in the 2022 shallow surveys due to our limited area, with the bulk of our sample concentrating around 30 mag (median and quartiles F277W 30.2 29.8 30.7 = mag).…”
Section: Selection Of Candidatesmentioning
confidence: 96%
See 1 more Smart Citation
“…Our deeper data allow us to find z > 8 galaxy candidates at fainter magnitudes, probing lower luminosities than previous works (see Section 4). Our sample, plotted in red in Figure 3, is compared with other photometrically selected candidates and the four first spectroscopic confirmations at z > 10 provided by JWST (Curtis-Lake et al 2023; Arrabal Haro et al 2023aHaro et al , 2023b as well as faint lensed galaxies above z ∼ 7 confirmed with NIRSpec spectroscopy (Langeroodi et al 2022;Carnall et al 2023;Roberts-Borsani et al 2023;Williams et al 2023). We have seven candidates in the magnitude regime probed in the 2022 shallow surveys due to our limited area, with the bulk of our sample concentrating around 30 mag (median and quartiles F277W 30.2 29.8 30.7 = mag).…”
Section: Selection Of Candidatesmentioning
confidence: 96%
“…However, different teams analyzing the same observations have only agreed on a few objects (Bouwens et al 2023a). The spectroscopic confirmation of z > 10 candidates is starting to be carried out with JWST/NIRSpec; however, it may require exposure times of tens or even hundreds of hours (Curtis-Lake et al 2023;Arrabal Haro et al 2023a; or taking advantage of lensing clusters, Roberts-Borsani et al 2023;Williams et al 2023), thus bringing into question the feasibility of obtaining robust samples composed of hundreds or even tens of z > 10 galaxies, with more promising results at 8 < z < 10 (Fujimoto et al 2023;Isobe et al 2023;Sanders et al 2023;Tang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the highest-redshift objects spectroscopically confirmed from the ground (Oesch et al 2015;Zitrin et al 2015;Roberts-Borsani et al 2016;Stark et al 2017) seem to hint at a harder UV spectrum than expected from typical stellar populations (Stark et al 2015a(Stark et al , 2015b, indicating possible AGN activity, Population III star contribution, or other hard ionizing photon sources (e.g., Laporte et al 2017;Mainali et al 2017;Matthee et al 2020). Observations with the JWST have already supplied unprecedented rest-frame UV and optical spectra for some very high-redshift galaxies (Roberts-Borsani et al 2023;Curtis-Lake et al 2023;Williams et al 2023) and might indeed supply new insight soon. In addition, objects that potentially bridge the typical high-redshift galaxy and AGN populations were also recently reported.…”
Section: Introductionmentioning
confidence: 95%
“…We plot this object onto the growing sample of known galaxies at high redshift in M U V -redshift space in Figure 2. At the other luminosity extreme among z > 9 sources is a highly magnified z = 9.76 galaxy also from the GLASS-JWST survey [14] with an intrinsic M U V = −17.35 (µ ∼ 13), demonstrating the dynamical range capabilities of the GLASS program and of JWST in general.…”
Section: Photometric Propertiesmentioning
confidence: 83%
“…With JWST commencing science operations in July 2022, progress has been rapid and transformational. Already in the first Cycle of science programs, JWST has built a convincing sample of z > 10 candidates based on NIRCam photometry [7][8][9][10][11][12], and a growing number of sources at z ≳ 8 are being confirmed spectroscopically with NIRSpec [13][14][15][16]. Surprisingly, the number density of (spectroscopically confirmed) high-redshift galaxies has been higher than expected by most models, in particular at the bright end of the luminosity function, possibly suggesting that we are missing key physical processes connected to the formation of first galaxies [17,18].…”
Section: Mainmentioning
confidence: 99%